Fundamentos jurídicos para reconocer la formación política en la Ley Universitaria N° 30220 del Perú - Ríos Rengifo, Alex Junior (2022)
The constant transformations that our society has undergone and the current political crisis in which we find ourselves as Peruvians, has led are to analyze the importance of education in our country, at all educational levels; however, my research emphasizes Higher University Education. This, because the State is not guaranteeing a comprehensive education and our legislation needs to be modified to generate in the student a greater critical, rational, ethical and moral sense; thus achieve, the full development of the personality of the human being, which is the future professional and citizen. The main objective of this research is to establish the legal foundations to recognize political training in University Law No. 30220 of Peru. The basic research method of exploratory level was used; legally dogmatic and sociological-functional. In that sense, it was obtained as a result, which constitute legal bases for the recognition of political training in University Law No. 30220, the principle of adaptability, legal obligations of the duties of the state, principle of freedom in teaching, principle of autonomy of the person, principle of the free development of the personality, principle of the superior interest of the student and principle of university autonomy.